2015
DOI: 10.1038/ncomms8349
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics enhanced by HCl doping triggers 60% Pauling entropy release at the ice XII–XIV transition

Abstract: The pressure–temperature phase diagram of ice displays a perplexing variety of structurally distinct phases. In the century-long history of scientific research on ice, the proton-ordered ice phases numbered XIII through XV were discovered only recently. Despite considerable effort, none of the transitions leading from the low-temperature ordered ices VIII, IX, XI, XIII, XIV and XV to their high-temperature disordered counterparts were experimentally found to display the full Pauling entropy. Here we report cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 47 publications
5
46
1
Order By: Relevance
“…Conversely, with a focus on exploring dynamical aspects leading to the ice V → ice XIII phase transition, here we report on the ambient-pressure dipolar response not only of undoped ice V but also of KOH and HCl doped crystals. This paper complements a recent experimental study of pure and doped ice XII [53]. For this high-pressure generated ice, HCl doping leads to the formation of ice XIV, a hydrogen ordered phase [5].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Conversely, with a focus on exploring dynamical aspects leading to the ice V → ice XIII phase transition, here we report on the ambient-pressure dipolar response not only of undoped ice V but also of KOH and HCl doped crystals. This paper complements a recent experimental study of pure and doped ice XII [53]. For this high-pressure generated ice, HCl doping leads to the formation of ice XIV, a hydrogen ordered phase [5].…”
Section: Introductionsupporting
confidence: 70%
“…[25] and ice XII(HCl) Ref. [53], which were found to eventually lead to the ordered phases ice XI and ice XIV, respectively. Hence, monitoring the dielectric response of ice V(HCl) down to lower temperatures allowed us to study the ordering transition in this ice phase, as will be demonstrated in the following.…”
Section: Results and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dashed lines refer to power laws ε ′′ ∝ ν -α as indicated. For comparison, frame (b) shows dielectric loss spectra for the crystalline ices IV, V, 51 VI, and XII 50 as well as for CO 2 -filled clathrate hydrate. Note that a peak maximum cannot be identified clearly for the data of ice VI and of the CO 2 -filled clathrate hydrate.…”
Section: Discussionmentioning
confidence: 99%
“…In the astrophysical literature (e.g., Ref. 33), such high-surface-area samples are often called porous ASW (p-ASW) and they are prone to an uncontrolled uptake of background gas 51 VI, and XII 50 are represented as symbols, those of LDA and HDA as dashed lines. The half-filled points for the CO 2 -filled clathrate hydrate and for ice VI were obtained by matching the high-frequency flank of their main process to that of the HGW sample.…”
Section: Discussionmentioning
confidence: 99%